(untitled) (International Journal of Engineering and Computer Science, 2018)
Video Streaming has become a major application in today’s IT enabled society by many users. WMV and MPEG are the formats which are used in real time streaming in Cloud Computing. In this paper I analyze the performance of WMV and MPEG video format streaming using Java Tool and Video Inspector Tool.